Acibenzolar-S-methyl treatment enhances antioxidant ability and phenylpropanoid pathway of blueberries during low temperature storage. (August 2019) - Ge, Yonghong; Tang, Qi; Li, Canying; Duan, Bin; Li, Xue; Wei, Meilin; Li, Jianrong
Abstract: Blueberry fruits were immersed in 100 mg/L acibenzolar-S-methyl (ASM) for 10 min and then stored at 4 °C with 40–50% relative humidity (RH) to investigate the changes of anti-oxidative enzyme activity, antioxidants and secondary metabolites in reactive oxygen species metabolism and phenylpropanoid pathway. The results indicated that ASM effectively enhanced the activity of superoxide dismutase, ascorbate peroxidase, catalase and the content of reduced glutathione and ascorbic acid in blueberries but decreased the content of H2 O2 . The activity of phenylalanine ammonialyase, polyphenol oxidase and the content of lignin, flavonoids, total phenolics and anthocyanin in blueberries were also enhanced by ASM treatment. These results suggest that postharvest ASM treatment could maintain the reactive oxygen species balance and enhance phenylpropanoid pathway to keep antioxidant ability of blueberries during low temperature storage. Highlights: ASM maintained the redox balance in blueberry fruit. ASM promoted the phenylpropanoid pathway. ASM has the potential to keep antioxidant ability of blueberries during low temperature.